Conto: uma autoanálise da prática pedagógica - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study presents a self-analysis of pedagogical practices developed during the mandatory supervised internship in 7th-grade and 1st-year high school classes. The qualitative, descriptive, and exploratory research aims to bridge theory and practice through the implementation of didactic sequences focused on reading, writing, and ludicity using the literary short story as a textual genre in portuguese lenguage. The theoretical framework encompasses concepts related to reading, writing, teaching methodologies, ludic activities, and the short story genre. The applied activities were evaluated using tools such as assessment rubrics, emphasizing the appropriateness of question design for reading tasks and compliance with the requirements of the writing production processes. Findings suggest that integrating ludic strategies with reflective and well-structured planning enhances student engagement and contributes to the overall effectiveness of classroom practices. The study concludes that theoretically grounded teacher self-assessment is a crucial element for the improvement of teaching performance and for adapting pedagogical methods as needed.
Keywords: Língua portuguesa; Conto; Atividades lúdicas; Educação básica; Portuguese language; Short story; Recreational activities; Basic education; LINGUISTICA, LETRAS E ARTES